Sosialisasi Dan Stimulasi Pembuatan Konten Digital Produk UMKM Kepada Siswa SMAK Yos Sudarso Kota Batam - Syafruddin Rais; Dailami.; Natal Olotua Sipayung (JURNAL KEKER WISATA, 2023)
Many MSME (Micro, Small and Medium Enterprises) actors are covered by their lack of knowledge about digital marketing and electronic commerce (e-commerce). Take advantage of the potential in digital marketing and how to create good digital content to attract customers. Based on various facts obtained from the field, it can be formulated that the problems that arise in the EPI (Excellent Preneur Indonesia) MSME community are: lack of content creation and content sharing for digital marketing content. This problem prompted the community service team to provide outreach regarding digital content creation for the development of the MSME community. The method used is in the form of lectures, then questions and answers, and practice of creating content. The outreach was attended by 25 participants and went smoothly. This service activity produced results, including being able to increase knowledge and motivation as well as participants' ideas for creating digital content for the business they were running and adjusted according to target customers.